Gifted & talented children with special educational needs : double exceptionality - Montgomery, Diane (David Fulton, 2003)
Gifted pupils who also have special needs often receive provision for the special need whilst the giftedness is overlooked. Children with such double exceptionality can become depressed, frustrated and misbehave, and may not fulfil their potential. Based on international research and practice, this practical text enables the reader to identify highly able pupils with special needs, such as ADHD, dyspraxia, dyslexia and Downs Syndrome, and then make provision for them within the mainstream school. The book offers three emerging themes: creating a positive, constructive and supportive learnin.